Features of the maintenance of microcells in an organism of the Russian sturgeon of northern part of the Caspian Sea - N. G. Shaboyants; S. V. Shipulin; S. A. Guseinova (Юг России: экология, развитие, 2015)
Microcells have special value for a modern condition of biosphere. They are not a part of organic connections of which fabrics of alive organisms consist, but at the same time are a necessary component of biocatalysts and bioregulators of the major physiological processes